Sumber Daya Teknologi Terhadap Pelaksanaan Kurikulum di Era Digital - Hasanbasri Hasanbasri; Parisyi algusyairi; Nurhayuni Nurhayuni; mudasir mudasir (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
The purpose of writing this work is to analyze technological resources for curriculum implementation in the digital era. The literature review includes scientific journals, books and literature related to education, technology and digital curriculum to gain in-depth insight into the use of technological resources in implementing curriculum in the digital era. Data collection methods involve analysis of official documents, such as government policies, and interviews with education and technology experts to understand the challenges and potential of implementing technology in curriculum contexts. The results of this work are a) Technology has a crucial role in increasing interactivity and personalization of learning, ensuring its effectiveness and providing unlimited access through resources such as digital libraries. Effective use of technology in the digital era has a significant positive impact, creating an adaptive learning environment and improving the overall quality of education. b) The integration of technology in education faces infrastructure barriers, insufficient educator training, limited policy support, and curriculum incompatibility. Solutions require holistic efforts, including infrastructure provision, comprehensive training, policy support, and external collaboration to create an innovative learning environment. c) The use of technology in education provides a positive impact and enriches the learning experience, with challenges such as gaps in access and educator training that can be overcome through a holistic approach and external collaboration, emphasizing awareness of the key role of policy, ongoing training and maintenance of technology as a vital foundation for the future an innovative and responsive educational future.